NILAI TAMBAH USAHA INDUSTRI TEMPE DAN STRATEGI PENGEMBANGANNYA (Studi Kasus Di Usaha Home Industri Tempe Bapak Syam Desa Sirnajaya Kecamatan Tarogong Kaler Kabupaten Garut) - MOCH HABIB ABDILAH; KARYANA KS; ANA YOHANA (OrchidAgri, 2023)
This research was conducted with the aim of knowing the business processing system of the tempe industry, to find out how much added value is obtained from processing soybeans into tempeh, and to determine the strategy for developing the tempe industry business. The data analysis used is a case study descriptive method. The results of the research value added tempeh business is Rp. 5.136/kg. And for the added value of the workers, namely Rp. 1.489/kg. As for the development method, it shows that the company's internal factors (strengths and weaknesses) reach -0.41, while the external factors (opportunities and threats) of the company reach 0.43. The strategy that needs to be implemented is the W-O (Weaknessis-Opportunity) strategy. The focus of this strategy is aimed at improving internal weaknesses by taking advantage of external opportunities. To obtain higher income, this business must increase production, as well as optimize sales by utilizing social media as a means of production.